Love, marriage, and Jewish families : paradoxes of a social revolution - Fishman, Sylvia Barack, 1942- (HBI series on Jewish women., 2015)
Illustrates the complex and diverse ways that Jews in the United States and Israel are reshaping dating, marriage, and family life-with some surprising consequences.